Anaemia and physical and mental health in the very old: An individual participant data meta-analysis of four longitudinal studies of ageing. (16th September 2020) - Palapar, Leah; Kerse, Ngaire; Rolleston, Anna; den Elzen, Wendy P J; Gussekloo, Jacobijn; Blom, Jeanet W; Robinson, Louise; Martin-Ruiz, Carmen; Duncan, Rachel; Arai, Yasumichi; Takayama, Midori; Teh, Ruth; et al.
Abstract: Objective: To determine the physical and mental health of very old people (aged 80+) with anaemia. Methods: Individual level meta-analysis from five cohorts of octogenarians (n = 2, 392): LiLACS NZ Māori, LiLACS NZ non-Māori, Leiden 85-plus Study, Newcastle 85+ Study, and TOOTH. Mixed models of change in functional ability, cognitive function, depressive symptoms, and self-rated health over time were separately fitted for each cohort. We combined individual cohort estimates of differences according to the presence of anaemia at baseline, adjusting for age at entry, sex, and time elapsed. Combined estimates are presented as differences in standard deviation units (i.e. standardised mean differences–SMDs). Results: The combined prevalence of anaemia was 30.2%. Throughout follow-up, participants with anaemia, on average, had: worse functional ability (SMD −0.42 of a standard deviation across cohorts; CI -0.59, -0.25); worse cognitive scores (SMD -0.27; CI -0.39, -0.15); worse depression scores (SMD -0.20; CI -0.31, -0.08); and lower ratings of their own health (SMD -0.36; CI -0.47, -0.25). Differential rates of change observed were: larger declines in functional ability for those with anaemia (SMD −0.12 over five years; CI -0.21, -0.03) and smaller mean difference in depression scores over time between those with and without anaemia (SMD 0.18 over five years; CI 0.05, 0.30). Conclusion: Anaemia in the very old is a common condition associated with worse functional ability, cognitive function, depressive symptoms, and self-rated health, and a more rapid decline in functional ability over time. The question remains as to whether anaemia itself contributes to worse outcomes or is simply a marker of chronic diseases and nutrient deficiencies.